2010
DOI: 10.2486/indhealth.ms1081
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Approach during Routine Follow-up is Effective for Obstructive Sleep Apnea Hypopnea Syndrome Subjects Receiving Nasal Continuous Positive Airway Pressure Treatment

Abstract: The present study investigated the effectiveness of a weight loss program during routine medical follow-up with regularity on promoting weight reduction in obese obstructive sleep apnea hypopnea syndrome (OSAHS) subjects receiving continuous positive airway pressure treatment (CPAP). A total of 10 male obese OSAHS subjects treated with CPAP were enrolled in the present study that was an intervention study without a control and had a pre-post test study design. The age was 50.7 (7.8) (mean (SD)) years, and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The flowchart of the search and selection of studies is shown in Figure . A total of 13 RCTs and 22 uncontrolled before‐and‐after studies were selected for inclusion. One non‐randomized study was considered an RCT as there were not differences between groups at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…The flowchart of the search and selection of studies is shown in Figure . A total of 13 RCTs and 22 uncontrolled before‐and‐after studies were selected for inclusion. One non‐randomized study was considered an RCT as there were not differences between groups at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Of studies investigating such approaches to improve OSA outcomes, interventions of greater success have commonly incorporated elements of very low caloric diets (Tuomilehto et al ., ; Yee et al ., ). Individual dietary and behavioural counselling has also been shown to have promising results (Fujii et al ., ). Whilst surgical approaches can be effective (Dixon et al ., ), it is not widely accessible and the most effective approach for achieving long‐term, sustained weight loss for people with OSA is not clear.…”
Section: Introductionmentioning
confidence: 97%
“…Αναλυτικότερα, 8 τυχαιοποιημένες ελεγχόμενες κλινικές δοκιμές (185,(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199) σύγκριναν μία εντατική παρέμβαση απώλειας βάρους (συνήθως χορήγηση διαιτών χαμηλών ή πολύ χαμηλών σε θερμίδες, σε συνδυασμό με συμβουλευτική για βελτίωση των συνηθειών του τρόπου ζωής, ή συμμετοχή σε ατομικές συμβουλευτικές συνεδρίες με στόχο τη μείωση της ενεργειακής πρόσληψης χωρίς χορήγηση υποθερμιδικής δίαιτας) με μία παρέμβαση ελέγχου (απλές συμβουλές για έναν υγιεινό τρόπο ζωής ή απουσία παρέμβασης), και ανέδειξαν την υπεροχή της πρώτης στη βελτίωση της βαρύτητας και της συμπτωματολογίας της ΑΑΥ. Επιπλέον, 19 κλινικές δοκιμές (201,202,(208)(209)(210)(211)(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226) εφάρμοσαν μια παρέμβαση απώλειας βάρους (κυρίως χορήγηση διαιτών χαμηλών ή πολύ χαμηλών θερμίδων, είτε αποκλειστικά είτε σε συνδυασμό με συμβουλευτική για βελτίωση των συνηθειών του τρόπου ζωής) σε ασθενείς με ΑΑΥ, απουσία ομάδας ελέγχου, και ανέδειξαν, επίσης, τα οφέλη της στη μείωση των απνοϊκών επεισοδίων και στη βελτίωση της οξυμετρίας, των συμπτωμάτων της ΑΑΥ, της αρχιτεκτονικής και της ποιότητας του ύπνου και της ποιότητας ζωής των ασθενών. Αξίζει να σημειωθεί ότι σε αρκετές από τις προαναφερθείσες μελέτες, η αρχική βαρύτητα της ΑΑΥ και το μέγεθος της απώλειας βάρους ήταν οι ισχυρότεροι προγνωστικοί παράγοντες για τη βελτίωση της βαρύτητας της νόσου.…”
Section: παρεμβάσεις απώλειας βάρουςunclassified